Original paperSide effects and allergy to selected cosmetic ingredients in persons with allergic diseases - Wojciechowska, Milena; Kołodziejczyk, Joanna; Mućka, Jacek; Gocki, Jacek; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Introduction : Cosmetics, even when used according to indications and manufacturer’s recommendations, often cause side effects, hypersensitivity and allergic reactions. Aim : To determine the prevalence of side effects and hypersensitivity after cosmetics use and allergy to selected cosmetic ingredients in persons with allergic diseases. Material and methods : The study included 50 patients of the Allergy Outpatient Clinic in Bydgoszcz, suffering from the following allergic diseases: asthma, pollinosis, allergic dermatitis, urticaria and atopic dermatitis. The study consisted of two stages. In the first stage, the subjects filled in a questionnaire on cosmetic product tolerance with the investigator’s help. Then the subjects underwent epidermal patch testing with selected cosmetic ingredients. Results : 78% of subjects reported side effects after cosmetic use. They were predominantly caused by face creams (56.4%). In 82% of patients who reported side effects the reactions were repeatable and had features of hypersensitivity. 14% of the whole group had positive results of epidermal patch tests. Conclusions : Allergy to cosmetic ingredients is an important, yet underestimated problem in the population of patients with allergic diseases. The prevalence of this problem needs to be monitored and the most common allergenic cosmetic ingredients need to be determined in order to limit (or even eliminate) their use by allergy patients.